2018
DOI: 10.1007/s12264-018-0297-4
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Endogenous Angiotensin-(1–7) in Hypothalamic Paraventricular Nucleus Attenuates High Salt-Induced Sympathoexcitation and Hypertension

Abstract: Angiotensin (Ang)-(1-7) is an important biologically-active peptide of the renin-angiotensin system. This study was designed to determine whether inhibition of Ang-(1-7) in the hypothalamic paraventricular nucleus (PVN) attenuates sympathetic activity and elevates blood pressure by modulating pro-inflammatory cytokines (PICs) and oxidative stress in the PVN in salt-induced hypertension. Rats were fed either a high-salt (8% NaCl) or a normal salt diet (0.3% NaCl) for 10 weeks, followed by bilateral microinjecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 46 publications
0
8
0
1
Order By: Relevance
“…Tempol mimics the role of superoxide dismutase in scavenging superoxide anions [41], and NAC is another antioxidant with superoxide scavenging properties [42]. Ang II is an important stimulus for superoxide anion production in the brain [43] and vasculature [44], and superoxide anion production in the PVN plays a role in the sympathetic activation in hypertension [45]. Furthermore, our previous study has shown that superoxide anions in the PVN contribute to the enhanced CSAR in chronic heart failure [25], so we further investigated whether this mechanism is involved in the ERR.…”
Section: Discussionmentioning
confidence: 99%
“…Tempol mimics the role of superoxide dismutase in scavenging superoxide anions [41], and NAC is another antioxidant with superoxide scavenging properties [42]. Ang II is an important stimulus for superoxide anion production in the brain [43] and vasculature [44], and superoxide anion production in the PVN plays a role in the sympathetic activation in hypertension [45]. Furthermore, our previous study has shown that superoxide anions in the PVN contribute to the enhanced CSAR in chronic heart failure [25], so we further investigated whether this mechanism is involved in the ERR.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroanatomical evidence has shown that renal afferent activity is closely connected with various sites in the brain associated with sympathetic outflow and cardiovascular regulation, including the nucleus of the solitary tract, rostral ventrolateral medulla, PVN, subfornical organ, and preoptic area [10]. The PVN is important in the control of cardiovascular activity and sympathetic outflow via its descending projections to the rostral ventrolateral medulla and intermediolateral column of spinal cord [40][41][42][43]. Stimulation of the renal afferent nerve altered the activity of 197 neurons in 407 neurons in the PVN, most of which were excited, but 8% were suppressed [44].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, long-term salt intake elevates reactive oxygen species (ROS) accumulation in the neurons, blood vessels, and kidneys, which takes part in the metabolic disorders and cardiovascular diseases process. Previous studies have also found that a high salt diet exacerbates oxidative stress and the inflammatory responses in the paraventricular nucleus (PVN) of the hypothalamus, an important area for the regulation of cardiovascular activity and blood pressure [ 20 , 21 , 22 , 23 , 24 , 25 ]. Ras-related C3 botulinum toxin substrate 1 (Rac1) is a vital NAD(P)H subunit that promotes ROS production.…”
Section: Introductionmentioning
confidence: 99%